Marine Renewable Energy Technology and Environmental Interactions - Shields, Mark A.; Payne, Andrew I.L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
It is now widely recognized that there is a need for long-term secure and suitable sustainable forms of energy. Renewable energy from the marine environment, in particular renewable energy from tidal currents, wave and wind, can help achieve a sustainable energy future. Our understanding of environmental impacts and suitable mitigation methods associated with extracting renewable energy from the marine environment is improving all the time, and it is essential that we be able to distinguish between natural and anthropocentric drivers and impacts. An overview of current understanding of the environmental implications of marine renewable energy technology is provided.
1. An Introduction to Marine Renewable Energy -- 2. The physics and hydrodynamic setting of marine renewable energy -- 3. Baselines and monitoring methods for detecting impacts of hydrodynamic energy extraction on intertidal communities of rocky shores -- 4.Assessing the impact of wind farms in subtidal, exposed marine areas -- 5.The influence of fisheries exclusion and addition of hard substrata on fish and crustaceans -- 6.Marine renewable energy, electromagnetic (EM) fields and EM-sensitive animals -- 7. Seabirds and marine renewables: Are we asking the right questions? -- 8. Marine renewable energy and environmental interactions: baseline assessments of seabirds, marine mammals, sea turtles and benthic communities on the Oregon shelf -- 9. Rethinking underwater sound-recording methods to work at tidal-stream and wave-energy sites -- 10. Tracking technologies for quantifying marine mammal interactions with tidal turbines: Pitfalls and possibilities -- 11. Strategic sectoral planning for offshore renewable energy in Scotland -- 12. Strangford Lough and the Sea Gen tidal turbine.
Keywords: Environment; Renewable energy resources; Aquatic ecology; Renewable energy sources; Alternate energy sources; Green energy industries; Marine sciences; Freshwater; Environment; Marine & Freshwater Sciences; Renewable and Green Energy; Freshwater & Marine Ecology; Electronic books